2013 Faculty Guide for First-Year Seminars - Kansas State University, K-State First (My University, 2013)
A guide for instructors teaching first-year seminars for K-State First at Kansas State University. This guide provides an overview of all K-State First programs, sample course descriptions and attendance policies, best practices, as well as specific guidelines and suggestions for in-class activities and co-curricular events, such as field trips and sample classroom policies.
Keywords: First-year seminars; Faculty development; First-year experience program; Guide; Brochures